THE RELATIONSHIP OF EXCLUSIVE BREASTFEEDING WITH THE INCIDENCE OF ACUTE RESPIRATORY INFECTIONS IN INFANTS AGED 6-12 MONTHS - Pratiwi, Andi Elsa Mulya; Rauly Ramadhani,; Utami Murti Pratiwi, (Alami Journal (Alauddin Islamic Medical) Journal, 2022)
The occurrences of acute respiratory infections in Indonesia has been recorded to be approximately 6 million cases in infants that Indonesia is ranked 6th in the world. World Health Organization (WHO) recorded that in developing countries, 15-20% of births were considered to be acure respiratory infections in which 40 out 1000 infant deaths in a year were caused by the infection. The major objective of this research was to investigate the relationship between breast feeding and the occurrences of upper respiratory tract infection in infants aged between 6-12 months. The data collection method used in this study was analytical observation. The samples used in this study were infants who experienced acute respiratory infections at Balangnipa Health Center in January to September 2021 and samples met the inclusion and exclusion criteria using the total of sample was 88 samples. The samples consisted of primary data were taken from questionnaires, while secondary data were gained from the patients’ medical records. The data were further analyzed by using the Chi-Square. The findings of this research indicated that with the Chi-Square test at a significance level of 5% (α = 0.05), the p-value obtained was 0.000 (P <0.05). Therefore, it could be concluded that there is a correlation between exclusive breast feeding and the occurrences of acute respiratory infections in infants.